I Did Not Eat Your Mother: can the voice of animals be heard in Iranian picturebooks?. (1st January 2018) - Izadi, Maryam
ABSTRACT: This paper discusses different aspects of relations between human and animal characters in picturebooks by Seyed Ali Akbar and Alizadeh (2008), Ranjbar and Keshmiri (2005), and Khosronejad and Masoumian (2004) using the theoretical framework of ecocriticism. Ecocritical scholars demonstrate how nature and man are represented in various cultural contexts. The study focuses on how animals are characterized and positioned in confrontation with humans and maintain their voices within dominant anthropocentric structures. Reading the picturebooks from the perspective of "logic of domination", consisting of alienation, hierarchy, and domination through a descriptive-interpretative approach, reveals that animal characters remain persistent in expressing themselves. It also shows they destabilize human patterns stemming from the objectification of non-human animals.